Educational Waqf Governance: A Philosophical-Empirical Study of Islamic Institutions in West Java, Indonesia - Radif Khotamir Rusli; Martin Roestamy; Abraham Yazdi Martin; Nova Monaya; Zahra Khusnul Lathifah; Ghada Abd Elsattar Mohammed Orabyd (Jurnal Ilmu Pendidikan, 2025)
This study examines the governance framework of educational waqf in West Java, Indonesia, through a philosophical-empirical mixed method analysis. West Java, hosting the largest concentration of Islamic educational institutions in Indonesia, provides a critical case study for understanding waqf governance dynamics. Using quantitative descriptive analysis of 9,310 pesantren and qualitative exploratory discussion, this research reveals that West Java contains 49.4% of Java's Islamic boarding schools, with an estimated 10,884 waqf-based educational institutions managing 45,000 hectares of waqf land valued at 2.85 trillion IDR. The study identifies significant governance challenges including legal certification (85/100 severity index), management capacity (70/100), and financial transparency (65/100). Findings indicate that while West Java demonstrates substantial waqf utilization (78% rate), integrated governance frameworks are essential for optimizing educational waqf potential. The philosophical foundation of waqf, rooted in Islamic jurisprudence and maqasid al-shariah, requires contemporary governance models that balance traditional values with modern administrative efficiency. This research contributes to the theoretical understanding of waqf governance while providing empirical evidence for policy development in Islamic educational finance.